A FRET-based fluorescent approach for labetalol sensing using calix[6]arene functionalized MnO2@graphene as a receptor. Issue 83 (22nd August 2016) - Ye, Hanzhang; Yang, Long; Zhao, Genfu; Zhang, Yanqiong; Ran, Xin; Wu, Shilian; Zou, Suo; Xie, Xiaoguang; Zhao, Hui; Li, Can-Peng
Abstract : A turn-on fluorescent sensing platform for labetalol has been developed based on competitive host–guest interaction between p-sulfonated calix[6]arene (SCX6) and target molecule by using SCX6 functionalized MnO2 @reduced graphene oxide as a receptor. Abstract : A turn-on fluorescent sensing platform for labetalol determination has been developed based on competitive host–guest interaction between p-sulfonated calix[6]arene (SCX6) and signal probe/target molecules by using SCX6 functionalized MnO2 @reduced graphene oxide (SCX6-MnO2 @RGO) as a receptor. Rhodamine 6G (R6G) and labetalol were selected as the probe and target molecules, respectively. When R6G enters into the SCX6 host, its fluorescence is quenched by MnO2 @RGO. However, on addition of labetalol to the preformed R6G·SCX6-MnO2 @RGO complex, the R6G molecule is displaced by labetalol from the host of SCX6, leading to a "switch-on" fluorescence response. This is due to the fact that the binding constant of the labetalol/SCX6 complex is much higher than that of R6G/SCX6. The fluorescence intensity of the SCX6-MnO2 @RGO·R6G complex increased linearly with increasing concentration of labetalol ranging from 1.0 to 18.0 μM. The proposed method showed a detection limit of 0.25 μM for labetalol. In addition, 2D NMR and molecular modeling studies indicated that the salicylamide part of the labetalol molecule inserted into the cavity of SCX6, while the phenylpropyl group located outside of the SCX6 host.